2014
DOI: 10.1093/jac/dku400
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of total and unbound darunavir in HIV-1-infected pregnant women*

Abstract: Darunavir AUC and Cmax were substantially decreased in pregnancy for both darunavir/ritonavir regimens. This decrease in exposure did not result in mother-to-child transmission. For antiretroviral-naive patients, who are adherent, take darunavir with food and are not using concomitant medication reducing darunavir concentrations, 800/100 mg of darunavir/ritonavir once daily is adequate in pregnancy. For all other patients 600/100 mg of darunavir/ritonavir twice daily is recommended during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 15 publications
8
46
0
Order By: Relevance
“…In the case of antiretrovirals, all studies had showed decreased drug exposure in pregnancy due to PK changes. While most of these studies reported adequate viral suppression and no mother-to-child HIV transmission [132,135,138], one study reported an increased viral load during pregnancy, with a few cases of neonatal transmission of the virus [150]. Conflicting clinical results were also reported for antimalarial drugs: while some studies reported equal parasite clearance time or no increase in treatment failure in spite of decreased exposure [182], others demonstrated a positive correlation between the decreased exposure and poor clinical outcome, reporting an increase in treatment failure or a decrease in post-treatment prophylactic effect [181,195].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of antiretrovirals, all studies had showed decreased drug exposure in pregnancy due to PK changes. While most of these studies reported adequate viral suppression and no mother-to-child HIV transmission [132,135,138], one study reported an increased viral load during pregnancy, with a few cases of neonatal transmission of the virus [150]. Conflicting clinical results were also reported for antimalarial drugs: while some studies reported equal parasite clearance time or no increase in treatment failure in spite of decreased exposure [182], others demonstrated a positive correlation between the decreased exposure and poor clinical outcome, reporting an increase in treatment failure or a decrease in post-treatment prophylactic effect [181,195].…”
Section: Discussionmentioning
confidence: 99%
“…This collection of PK data could prove to be a decision support base for future attempts to tailor medication prescription for pregnant women to achieve target serum concentrations; however, one must take into account that many studies often report undiminished drug efficacy despite the aforementioned pregnancy-associated PK changes [132,135,138,145,146,163,172,177]. …”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previously published case reports and smaller series of patients. 10-16 Zorrilla, et al, reported a decrease of 17-24% in darunavir AUC in 14 women dosed twice daily in the second and third trimesters. 15 Colbers, et al reported a mean decrease in darunavir AUC of 34% in 6 women with twice daily dosing and 22% in18 women with once daily dosing in the third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Published data describing darunavir pharmacokinetics during pregnancy are limited. 10-16 The primary objectives of this study were to describe darunavir pharmacokinetics in HIV-infected pregnant women receiving once and twice daily dosing and to determine if standard doses of darunavir produce equivalent drug exposure during pregnancy to that in nonpregnant adults. We also sought to evaluate transplacental passage of darunavir by comparing concentrations in cord blood and maternal blood at delivery.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of pregnancy induced CYP450 enzyme induction, the standard adult dose of ritonavir (RTV)-boosted DRV (DRV/r) of 800mg/100mg daily results in inadequate DRV exposure during the third trimester [21, 32*, 33*]. A twice daily dose of DRV/r (600mg/100mg) is recommended instead, and although this dose also results in reduced exposure during the third trimester compared to post-partum, it is thought to be adequate [34].…”
Section: Universal Art Regimens: Considerations For Pregnant and Breamentioning
confidence: 99%